Increased lung inflammation with oxygen supplementation in tracheotomized spontaneously breathing rabbits: an experimental prospective randomized study - Machado, H. (2014)
BACKGROUND: Mechanical ventilation is a well-known trigger for lung inflammation. Research focuses on tidal volume reduction to prevent ventilator-induced lung injury. Mechanical ventilation is usually applied with higher than physiological oxygen fractions. The purpose of this study was to investigate the after effect of oxygen supplementation during a spontaneous ventilation set up, in order to avoid the inflammatory response linked to mechanical ventilation. METHODS: A prospective randomised study using New Zealand rabbits in a university research laboratory was carried out. Rabbits (n = 20) were randomly assigned to 4 groups (n = 5 each group). Groups 1 and 2 were submitted to 0.5 L/min oxygen supplementation, for 20 or 75 minutes, respectively; groups 3 and 4 were left at room air for 20 or 75 minutes. Ketamine/xylazine was administered for induction and maintenance of anaesthesia. Lungs were obtained for histological examination in light microscopy. RESULTS: All animals survived the complete experiment. Procedure duration did not influence the degree of inflammatory response. The hyperoxic environment was confirmed by blood gas analyses in animals that were subjected to oxygen supplementation, and was accompanied with lower mean respiratory rates. The non-oxygen supplemented group had lower mean oxygen arterial partial pressures and higher mean respiratory rates during the procedure. All animals showed some inflammatory lung response. However, rabbits submitted to oxygen supplementation showed significant more lung inflammation (Odds ratio = 16), characterized by more infiltrates and with higher cell counts; the acute inflammatory response cells was mainly constituted by eosinophils and neutrophils, with a relative proportion of 80 to 20% respectively. This cellular observation in lung tissue did not correlate with a similar increase in peripheral blood analysis. CONCLUSIONS: Oxygen supplementation in spontaneous breathing is associated with an increased inflammatory response when compared to breathing normal room air. This inflammatory response was mainly constituted with polymorphonuclear cells (eosinophils and neutrophils). As confirmed in all animals by peripheral blood analyses, the eosinophilic inflammatory response was a local organ event.